The Older Adult Experiencing Sepsis. Issue 2 (April 2015) - Englert, Nadine C.; Ross, Carl
<x xml:space="preserve">Abstract</x> Sepsis is a potentially fatal response to infection affecting patients across the life span. Sepsis can progress from systemic inflammatory response to severe sepsis and septic shock if not recognized promptly and managed effectively. Risk factors for sepsis include age, gender, the presence of invasive devices (eg, urinary catheters), and chronic medical conditions (eg, chronic obstructive pulmonary disease). Sepsis awareness is essential and includes identification of population-focused risk factors, recognition of clinical signs and symptoms, and timely implementation of interventions. The purpose of this article was to examine sepsis in older adults, including prevalence, atypical presentation of the condition, and considerations for sepsis management in the elderly population.